Implementation and evaluation of a Collaborative Learning in Practice (CLiP) placement pilot for physiotherapy students in an acute hospital setting - Dunford, Alex; Uren, Claire; Brunt, Hilary; Harry, Rosie (International Journal of Practice-based Learning in Health and Social Care, 2025)
The purpose of this paper is to discuss the implementation and evaluation of a Collaborative Learning in Practice (CLiP) placement pilot for physiotherapy students. This took place on an acute ward setting at a secondary care district hospital in the Southwest of England. Participants included two second year physiotherapy students and two practice educators. The physiotherapy CLiP placement ran alongside an established nursing CLiP placement for six weeks. Feedback was gained from the physiotherapy students using a post-placement questionnaire which included a mix of open and closed questions. Informal feedback was gained from the practice educators via email and meetings. The placement feedback gained highlights the benefits of using a CLiP model for student physiotherapy practice placements. The CLiP model promoted the students’ development of autonomy, caseload management, person centred care and communication, which are essential skills for qualification. Challenges included preparing and adjusting to the CLiP model. More research is needed to explore the effectiveness of CLiP for physiotherapy students, however this pilot identified that it is important that the most appropriate ward setting is identified and that adequate training and organisation has been put in place before the placement commences. This work highlights that a CLiP placement model can be beneficial for physiotherapy student placements and could be considered to help increase placement capacity. It also provides some guidance to enable others to implement the CLiP model.